Representative studies on victimisation: research findings from Germany - Pfeiffer, Christian; Baier, Dirk (Interdisziplinäre Beiträge zur kriminologischen Forschung, 2016)
Representative studies on crime and its development have so far been rare in Germany. A major focus of the research work of the Lower Saxony Criminological Research Institute, in which all the articles presented here were written, is on the subject of victimization. In recent years, studies on risk factors of victimization, victimization of different population groups and consequences of victimization have been conducted here. All contributions to the book present findings from empirical research projects. On the one hand, these are based on extensive standardized surveys, on the other hand, they are also based on interview studies with a small number of respondents. With contributions from: Dirk Baier, Steffen Bieneck, Bettina Doering, Karoline Ellrich, Sandra Fernau, Michael Hanslmaier, Theresia Höynck, Stefanie Kemme, Christian Pfeiffer, Susann Prätor, Lena Stadler, Ulrike Zähringer, Bettina Zietlow